Anorexia and Young Womens’ Personal Networks: Size, Structure, and Kinship - Mikhaylova, Oxana; Dokuka, Sofia (Frontiers in Psychology, 2022)
Anorexia is a serious threat to young women's well-being worldwide. The effectiveness of mental health intervention and treatment is often evaluated on the basis of changes in the personal networks; however, the development of such measures for young women with anorexia is constrained due to the lack of quantitative descriptions of their social networks. We aim to fill this substantial gap. In this paper, we identify the basic properties of these women`s personal networks such as size, structure, and proportion of kin connections. The empirical analysis, using a concentric circles methodology, is based on 50 ego networks constructed on data drawn from interviews with Russian-speaking bloggers who have been diagnosed with anorexia and write about this condition. We conclude that young women with anorexia tend to support a limited number of social ties; they are prone to select women as alters, but do not have a preference to connect to their relatives. Further research is needed to elucidate whether these personal network characteristics are similar among women with anorexia who belong to different age, ethnic, cultural and income groups.